Electronic-Based Mathematics Learning for Students' Creative Thinking Ability - Novi Susanti; Ria Erviana (Numerical: Jurnal Matematika dan Pendidikan Matematika, 2020)
The learning process is one of the essential things in students' success in obtaining the material they get, especially during the Covid-19 pandemic. Many students cannot carry out face to face in class. Therefore educators must provide the right method. So, students can understand the material it provides. Educators have used various ways not to feel bored, using the e-learning method. The study aims to determine Electronic-Based Mathematics Learning (EBML) for students' creative thinking ability in Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Muhammadiyah Pagaralam. The method used is the quasi-experimental method in the one-shot case study category. The study population was all students of the Mathematics Education Study Program of STKIP Muhammadiyah Pagaralam. The study results because of the indicator creative thinking indicators: fluent review 69.44%, flexible thinking 71.76%, original thought 74.92%, and elaborative thinking 88.19%. It is obtaining an average value of students amounted to 76,08%, it is categorized as useful. EBML is designed to simplify and shorten the learning process. So, it becomes more efficient. It is also to train students to be more independent in gaining knowledge to reach a wider geographical area, both in discussions and references. The EBML is applied to students’ creative think in understanding the material presented.